The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2215/cjn.04921107
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking Glucose Metabolism Alterations in Stable Renal Transplant Recipients

Abstract: Background and objectives: Emerging information indicates that glucose metabolism alterations are common after renal transplantation and are associated with carotid atheromatosis. The aims of this study were to investigate the prevalence of different glucose metabolism alterations in stable recipients as well as the factors related to the condition.Design, setting, participants, & measurements: A multicenter, cross-sectional study was conducted of 374 renal transplant recipients without pre-or posttransplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
3
14
0
2
Order By: Relevance
“…Overall, the reported prevalence of abnormal glucose metabolism was remarkably similar to the present results and ranged from 32 (28) to 51% (27). Our previous OGTT-based analysis of TIP study control patients at 3 months posttransplantation, however, showed 84% abnormal glucose metabolism, with 52% NODAT (16).…”
Section: Discussionsupporting
confidence: 89%
“…Overall, the reported prevalence of abnormal glucose metabolism was remarkably similar to the present results and ranged from 32 (28) to 51% (27). Our previous OGTT-based analysis of TIP study control patients at 3 months posttransplantation, however, showed 84% abnormal glucose metabolism, with 52% NODAT (16).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, only FPG was considered, and previous studies showed that postprandial hyperglycemia is common after transplantation even in patients with normal FPG (19). Perhaps, glycated hemoglobin may be a better marker of CV risk than FPG levels in transplant patients (20, 21), but unfortunately, this parameter was not available for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Additional measures to improve cardiovascular outcomes include oral glucose tolerance tests to diagnose impaired glucose metabolism adequately, and strict glucose control to reduce the risks associated with hyperglycemia and NODAT [46]. Sharif et al .…”
Section: Strategies To Minimize Cardiovascular Riskmentioning
confidence: 99%